Variations in terrigenous input into the eastern Equatorial Atlantic over 120ka: Implications on Atlantic ITCZ migration. (November 2018) - Akinnigbagbe, Akintoye E.; Han, Xiqiu; Fan, Weijia; Tang, Yong; Adeleye, Adedayo O.; Jimoh, Rasheed O.; Lou, Zhanghua
Abstract: Variation in the location of the Intertropical Convergence Zone (ITCZ) in eastern equatorial Atlantic (EEA) drastically affects rainfall in equatorial Africa and hence sedimentation on the African margin. Sediment core DY26III-Nig-S60-GC2 taken from the slope of the EEA offshore Nigeria (4°28′56′′.388′E, 3°33′10′′.764′N; water depth: 2946 m) was studied to decode the climatological response to the ITCZ migration in the past 120 ka. Based on oxygen isotope stratigraphy and radiocarbon dating, the sedimentation rates of this core range from 0.64 to 6.90 cm/ka and average of 3.17 cm/ka. The periods MIS 2, MIS 4 and MIS 5b from our studied core are characterized by Minima of Fe/K and maxima of K/Al, Ti/Al and magnetic susceptibility along with more kaolinite. This reflects a period when the region supposedly dominated by less precipitation and strong trade winds which suggest southward position of the ITCZ. Conversely, the periods MIS 1, MIS 3 and MIS 5a exhibit an opposite trend; these wet periods are of weak trade winds and northerly ITCZ excursion. Fluctuations in Fe/K, K/Al and Ti/Al records reflect changes in the low-latitude insolation cycle (23 kyr) and thus indicate a close coupling between terrigenous input and climate changes. This work thus highlights the importance of the terrigenous input as a prerequisite for the interpretation of ITCZ position in the EEA. Highlights: The Gulf of Guinea ITCZ migration affects rainfall pattern and soil weathering. K/Al and Ti/Al contents maximum occurred during MIS 2, MIS 4 and MIS 5b. The MIS 2, MIS 4 and MIS 5b marked periods of southward position of the ITCZ. MIS 1, MIS 3 and MIS 5a exhibits an opposite trend.